Multiple Fano Resonances Based on End-Coupled Semi-Ring Rectangular Resonator - Yihong Fang; Kunhua Wen; Zhengfeng Li; Bingye Wu; Li Chen; Jinyun Zhou; Dongyue Zhou (IEEE Photonics Journal)
In this paper, multiple Fano resonances based on semi-ring-rectangular composite cavity (SRRCC) structure are numerically investigated and explained by the finite-difference time-domain method and the multiple interference coupled mode theory method. High refractive-index sensitivities and high figure of merits (FOMs) are obtained in SRRCC system, and thus it may be preferred in the chip-scale optical sensing area. Besides, the phase response and the delay time within the Fano resonant windows are also investigated. Additionally, two more Fano resonances with high sensitivities and FOMs emerge through adding a new semi-ring cavity. These structures show widely applications in the sensing area and promote development of on-chip integrated photonics.